Fireless Brick Making using Water Treatment Sewage Sludge with MICP Action - Saputri, Evi Ari Ayu; Indriani, Andy Marini; Utomo, Gunaedy (Universitas Negeri Padang, 2023)
Bricks materials used in making the walls of building. Currently, brick making has new innovations. As in this study using water treatment sludge waste and bacillus subtilis bacteria. Sludge waste done with percentage of 20% and bacillus subtilis bacteria much as 6%. The process adding bacteria called the Microbially Induced Calcite Precipitation (MICP) process. The process to increase compressive strength clay soil. The purpose study to determine effect of Bacillus subtilis bacteria on the strength bricks using mud and the strength of bricks with bacterial reinforcement. The results showed the compressive strength did not the specifications, where value of the compressive strength of bricks in accordance with SNI 15-2094-2000 is 50 kg / cm². And results of compressive strength only amounted to 22.82 kg / cm² in the 28-day curing period. For compressive strength using mixture of bacteria produces highest strength value the 4-day culture period of 28.11 kg kg/cm².